2015
DOI: 10.1039/c5cc06824j
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing metal-coordinated hydrogels using nucleotide ligands

Abstract: A supramolecular gel formed by Zn 2+ coordination with adenosine monophosphate (AMP) is reported. The adenine base, the monophosphate, and Zn 2+ are all important for gel formation. Mechanically disrupted gels can re-form upon centrifugation; applications of this gel for guest molecule entrapment are explored.Supramolecular gels have received considerable attention in recent years both as intriguing examples of self-assembly and as a means of creating smart materials.1-5 These gels are formed by noncovalent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 41 publications
(62 reference statements)
1
73
0
Order By: Relevance
“…39 Interestingly, precipitation occurred by increasing the HEPES concentration ( Figure 1A). With 35 mM HEPES, yellow precipitants formed in a few minutes after adding FeCl3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…39 Interestingly, precipitation occurred by increasing the HEPES concentration ( Figure 1A). With 35 mM HEPES, yellow precipitants formed in a few minutes after adding FeCl3.…”
Section: Resultsmentioning
confidence: 99%
“…36 We recently found that Zn 2+ coordinates with adenosine monophosphate (AMP) to form hydrogels. 39 In this work, since we are interested in coating iron oxide NPs, the most appropriate metal is iron. Since Fe 2+ is easy oxidized in air, we tested Fe 3+ first.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, various types of biomolecules, such as nucleotides [34], proteins [35], peptides [36], amino acids [37] and nucleobases [38] have been used as the ligands to construct CPs. It also has been demonstrated that some CPs are capable of adsorbing and entrapping a broad range of molecules, due to their good biocompatibility and porosity [34,39]. Adenine, as an important naturally occurring nitrogen heterocycle present in nucleic acids [40], has multiple possible metal-binding modes [41][42][43].…”
Section: Introductionmentioning
confidence: 99%